(untitled) (Research, Society and Development, 2021)
The acceleration of modern life increases the search for facilities, directly affecting people’s diet. In this context, processed and industrialized foods are highlighted, given the practicality of their preparation. One of the problems around these foods is the large amount of sodium in their composition, both to give more flavor to the food and to keep them in their packaging. The exaggerated consumption of these foods is notorious, especially by adults. Thus, this paper aims to describe the impact of sodium consumption in the adult Brazilian population, reporting the main health consequences of its high intake. For this, an integrative literature review was carried out in a time frame from 2003 to 2021, obtaining results that generated discussions regarding sodium in the body and foods, the importance of labeling and the consequences of high sodium consumption. It was found that high sodium content can trigger diseases linked to hypertension, kidney diseases, stomach cancer, among others. And, despite the existence of specific regulations on the labeling of packaging, there is still a need for improvements, especially around the legibility of the labels, thus facilitating access to read them. Thus, the importance of raising the population’s awareness around the topic was observed, as only access to knowledge and information regarding what is consumed makes it possible to reduce the amount of sodium intake, directly impacting the quality of life of Brazilian adults.